VD_FINDINFO AM 21/20 - 36/2020 vom 7. Dezember 2020 - VD Tribunal cantonal (2020)
AM, ASSURANCE-MALADIE PRIVÉE, CHOIX DU MÉDECIN, MÉDECIN, MÉDECINE GÉNÉRALE | 41 al. 1 LAMal, 41 al. 4 LAMal, 62 al. 1 LAMal, 62 al. 3 LAMal, 24 al. 1 LPGA